Alpine ice-core evidence for the transformation of the European monetary system, AD 640-670 - Loveluck, Christopher; Hoffmann, Helene (Antiquity, 2018)
, The seventh-century AD switch from gold to silver currencies transformed the socio-economic landscape of North-west Europe. The source of silver, however, has proven elusive. Recent research, integrating ice-core data from the Colle Gnifetti drill site in the Swiss Alps, geoarchaeological records and numismatic and historical data, has provided new evidence for this transformation. Annual ice-core resolution data are combined with lead pollution analysis to demonstrate that significant new silver mining facilitated the change to silver coinage, and dates the introduction of such coinage to c. AD 660. Archaeological evidence and atmospheric modelling of lead pollution locates the probable source of the silver to mines at Melle, in France.